Energetic Effects of Whale-Watching Boats on Humpback Whales on a Breeding Ground - Villagra, Damian; García-Cegarra, Ana; Gallardo, Diego I.; Pacheco, Aldo S. (Frontiers in Marine Science, 2021)
Interactions between whale-watching boats and cetaceans can lead to changes in their behaviour. From a management perspective, it is important to understand how this type of disturbance can be translated into physiological effects, such as changes in their energetic metabolism. Humpback whales (Megaptera novaeangliae) typically do not feed while in breeding grounds, thus they depend on finite energy reserves. The effect of whale-watching boats on the energetic metabolism of humpback whales, in the breeding ground of northern Peru (4°10'35"S, 81°08'03"W) was evaluated. Groups of humpback whales were tracked from land, under the following scenarios: with, without, and before-during-after the presence of whale-watching boats. Mass-specific cost of transport (COT) was used as a proxy of energetic efficiency and calculated from swimming speed and breath frequency estimations. No differences were detected in breath frequency, swimming speed, and COT when comparing whales with and without boats. However, in the presence of boats, swim speed increased, and COT decreased as the number of boats increased. Exponential increment in breathing frequency at higher swimming speed was not detected. The absence of swimming speeds beyond the assumed optimal range suggested no shifts into metabolic inefficiency. Our results suggest optimal swimming speed between 2 and 4.05 m/s, representing COT values between 0.020 to 0.041 J×(kg×m)-1. In light of our results, we encourage the implementation of regulations of the activity, particularly limiting the number of boats interacting with the same group of humpback whales.